Risk of hip fracture in patients on hemodialysis versus peritoneal dialysis: A meta-analysis of observational studies - Boonphiphop Boonpheng (2020)
© 2019 Chinese Cochrane Center, West China Hospital of Sichuan University and John Wiley & Sons Australia, Ltd Background: Bone and mineral metabolism disorders are common among end-stage renal disease (ESRD) patients, which could lead to hip fracture. It is unclear whether the hip fracture risk is different among patients on hemodialysis (HD) versus peritoneal dialysis (PD). This meta-analysis was conducted to evaluate the hip fracture risk in ESRD patients on HD, when compared to PD. Methods: A literature review was conducted in EMBASE, MEDLINE, and Cochrane databases through January 31, 2018 to identify studies that appraised the rate or risk of hip fracture among patients on HD, when compared to PD. Effect estimates from the individual studies were derived and consolidated utilizing random-effect, generic inverse variance approach of DerSimonian and Laird. Results: Five cohort studies with 1 276 677 ESRD patients were enrolled. HD status was associated with a significantly higher risk of hip fracture with the pooled odds ratio (OR) of 1.61 (95% confidence interval [CI] 1.50-1.73, I2 = 10.0%), compared with PD. When the analysis was limited to studies with confounder-adjusted analysis, the pooled OR of hip fracture among HD patients was 1.57 (95% CI 1.43-1.72, I2 = 13.6%). Funnel plots and Egger's regression test demonstrated no significant publication bias in our meta-analysis. Conclusions: Among ESRD patients, HD status is associated with a 61% higher risk of hip fracture compared to PD.